Coordination polymers fabricated from Cd(NO3)2 and N, N′, O-pincer-type isonicotinoylhydrazone-based polytopic ligands – an insight from experimental and theoretical investigations. Issue 20 (5th May 2022) - Mahmoudi, Ghodrat; Akbari Afkhami, Farhad; Khandar, Ali Akbar; White, Jonathan M.; Maniukiewicz, Waldemar; Babashkina, Maria G.; Mitoraj, Mariusz P.; Sagan, Filip; Safin, Damir A.
Abstract : Three new Cd(ii ) coordination polymers based on isonicotinohydrazide ligands (HL I, HL II ) differing in the presence of a methyl unit have been obtained and extensively characterized by experimental and computational approaches. Abstract : Three cadmium(ii ) coordination polymers, namely {[Cd(HL I )(NO3 )2 ]·0.5MeOH} n (1 ), {[Cd(HL II )(NO3 )2 ]·EtOH} n (2 ), and [Cd2 (L II )2 (NO3 )2 ] n (3 ), have been self-assembled from Cd(NO3 )2 and N, N ′, O -pincer-type isonicotinoylhydrazone-based ditopic ligands (HL I = N′ -(pyridin-2-ylmethylene)isonicotinohydrazide and HL II = N ′-(1-(pyridin-2-yl)ethylidene)isonicotinohydrazide) and have been characterized experimentally and by DFT computations. In compounds 1 and 2, the corresponding ligand is coordinated to the metal center in the keto form and acted as a tetradentate chelating–bridging agent in which the nitrogen atom of the 4-pyridine ring is coordinated to the cadmium center of the neighboring unit, yielding 1D zig-zag coordination polymers. In compound 3, the ligand was singly-deprotonated and is coordinated in the enolic form with the nitrate ion further acted as a bridging agent, yielding a 2D network. It is revealed by the extended transition state natural orbital for chemical valence (ETS-NOCV) charge and energy decomposition scheme that typical hydrogen bonds O–H⋯O and N–H⋯O, which constitute the networks of 1 and 2, though dominated by a classic Coulomb term, are characterized by an equally important London dispersion constituent due to extra π⋯π and C–H⋯X contacts (X = O, H–C, H–N). The architecture of 3 is due to ionic and dative-covalent Cd–X (X = N, O) bonds as well as London dispersion-driven homopolar dihydrogen C–H⋯H–C and C–H⋯O interactions. NOCV-based representation allowed us to determine that hydrogen bonds O–H⋯O are twice weaker than the corresponding N–H⋯O in the networks of 1 and 2 .